An Introduction to Mesozoic Faunas and Floras of Indonesia - J.T. (Han) van Gorsel (Berita Sedimentologi, 2014)
This paper is a continuation of the paper on Paleozoic and reviews the main Mesozoic fossil groups of Indonesia and key literature, with focus on groups that are of biostratigraphic or paleobiogeographic significance.